METHODS OF ORGANIZING IN ENDURANCE AND PROGNOSIS OF RESULTS IN WRESTLING OF GREEK-ROME STYLE - Mališa Radović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Wrestling belongs to the groups of very complex ,semistructual, non-rhytmical sports. Physical capability of wrestler and his sport's level depend from quality of his physical capability. It depends also from level of functional possibility in organism. Top results in \vrestling are closely connected vvith the level of development in special endurance, so training process pays attention to improve these tvvo characters. Increasing of special endurance depends also from using objective information about changing functional condition of vvrestler. Very important role in vvrestling possesses dynamic elements vvhich need strong strain and strain the muscles. The physical capabilities are complexity engaged in the fight and different situations which appear during the fight need strong muscles -joint's sensation and resourcefulness to reach the top results.